A surface metal ion-modified 3D-printed Ti-6Al-4V implant with direct and immunoregulatory antibacterial and osteogenic activity - Wu, Yipeng; Shi, Xiangwen; Wang, Jianjun; Li, Yang; Wu, Jiang; Jia, Daqi; Bai, Yan; Wu, Xiaopei; Xu, Yongqing (Frontiers in Bioengineering and Biotechnology, 2023)
The high concentration of antibacterial metal ions may also indicate unavoidable toxicity to cells and normal tissues. The application of antibacterial metal ions to activate the immune response and induce macrophages to attack and phagocytose bacteria is a new antimicrobial strategy. In this study, 3D-printed Ti-6Al-4V implants modified by copper, and strontium ions combined with natural polymers were designed to treat implant-related infections and osseointegration disorders. The applied polymer-modified scaffolds can rapidly release copper and strontium ions in large quantities. During the process, copper ions were used to promote the polarization of M1 macrophages, induce a proinflammatory immune response to inhibit infection and achieve immune antibacterial activity. Meanwhile, copper and strontium ions promote macrophages to secrete bone-promoting factors, induce osteogenesis and have immunomodulatory osteogenesis. This study proposes immunomodulatory strategies based on the immunological characteristics of target diseases and provide ideas for the design and synthesis of new immunoregulatory biomaterials.